2005
DOI: 10.2465/jmps.100.116
|View full text |Cite
|
Sign up to set email alerts
|

The Kobe CK carbonaceous chondrite: petrography, mineralogy and metamorphism

Abstract: A petrographic and mineralogical study of Kobe indicates that it can be classified as a CK4 carbonaceous chondrite. CK chondrites differ from other groups of carbonaceous chondrites, because all normal CK chondrites have been thermally metamorphosed. Olivine and plagioclase are the two most abundant minerals in Kobe. Olivine is very homogeneous in composition, which is consistent with the metamorphic feature of Kobe. However, plagioclase shows large grain to grain compositional variations. The matrix and chond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…The textures and chemical compositions of constituent minerals of the Kobe meteorite are described in detail by Tomeoka et al (2005). Consistent with this earlier study, plagioclase in the PTS analyzed in the present study occurs mainly in the matrix as irregularly shaped grains that are typically 50 150 μm in size.…”
Section: Materials and Experimentssupporting
confidence: 77%
See 3 more Smart Citations
“…The textures and chemical compositions of constituent minerals of the Kobe meteorite are described in detail by Tomeoka et al (2005). Consistent with this earlier study, plagioclase in the PTS analyzed in the present study occurs mainly in the matrix as irregularly shaped grains that are typically 50 150 μm in size.…”
Section: Materials and Experimentssupporting
confidence: 77%
“…Figure 2 shows a histogram of the An mol% of all plagioclases randomly analyzed in this study. The data extend over a wide range from An 23.4 − 90.4 , as reported previously by Tomeoka et al (2005); however, approximately 70% of analyses fall in the range An 50 − 65 . Accordingly, as the crystals to be analyzed in terms of structural state fall in the range An 54.7 − 63.3 , they can be considered to be representative of plagioclase from the Kobe meteorite.…”
Section: Resultsmentioning
confidence: 48%
See 2 more Smart Citations
“…A scanning electron microscope (SEM) study of the Kobe CK4 chondrite (Tomeoka et al, 2001(Tomeoka et al, , 2005 revealed that it contains an abundance of unusual olivine in both the matrix and chondrules, and this contains numerous small vesicles and inclusions of magnetite, pentlandite, and a variety of other minerals. In the Kobe matrix, the vesicular olivine fills interstices of nonvesicular olivine grains forming a complex network of veinlets.…”
Section: Introductionmentioning
confidence: 99%